2018
DOI: 10.1080/10872981.2018.1485432
|View full text |Cite
|
Sign up to set email alerts
|

Student response to reports of unprofessional behavior: assessing risk of subsequent professional problems in medical school

Abstract: Background: An early concern note (ECN) program is used by some medical schools to identify, counsel, and intervene when students exhibit unprofessional behavior. Student maturity, insight, propensity for reflection, and receptiveness to feedback have been suggested as predictors of future behavior. Objective: We hypothesized that (a) classifying students with a first ECN based on their response to the report would identify students at risk of repeat ECNs better than the action that prompted it and (b) receipt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Medical professionalism can be assessed by observing behaviours. Various researchers have grouped such behaviours into categories or patterns (Teherani et al 2009;Hays et al 2011;Mak-van der Vossen et al 2016;Ainsworth and Szauter 2018). The reason for using this approach is that such patterns are easier to recognize for an educator than single behaviours, and also, that different patterns might need different guiding or remediating activities.…”
Section: Profiles Of Unprofessional Behaviourmentioning
confidence: 99%
See 2 more Smart Citations
“…Medical professionalism can be assessed by observing behaviours. Various researchers have grouped such behaviours into categories or patterns (Teherani et al 2009;Hays et al 2011;Mak-van der Vossen et al 2016;Ainsworth and Szauter 2018). The reason for using this approach is that such patterns are easier to recognize for an educator than single behaviours, and also, that different patterns might need different guiding or remediating activities.…”
Section: Profiles Of Unprofessional Behaviourmentioning
confidence: 99%
“…Research-generated profiles of student behaviours are based on two factors: the student's reflectiveness and their adaptability (see Figure 2). Reflective behaviour (listening to feedback and willingness and ability to incorporate it in future behaviour) is the basis of these profiles, as it predicts the future professionalism of a student better than the common engagement behaviours educators tend to denominate Hoffman et al 2016;Krzyzaniak et al 2017;Ainsworth and Szauter 2018). A student's behavioural profile can become apparent over time in different ways: by one teacher observing the student over a period of time; by forward feeding of performance from present teachers to new teachers, or by combining evaluations from different teachers by someone who has an oversight of the assessments.…”
Section: Profiles Of Unprofessional Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the codes identified in the literature review phase of our study discuss unprofessional behaviors related to the domain of honor and integrity. In similar cases, Ainsworth’s article in 2018 showed that the most reported unprofessional behaviors pertained to the domain of integrity [ 42 ]. Also, the code “observing honesty and trustworthiness in actions, speech and writing” related to the domain of honor and integrity was one of the highest prioritized codes with high prevalence according to clinical faculty members.…”
Section: Discussionmentioning
confidence: 99%
“…These residents did sometimes rationalize away their lapses by viewing them as minor issues, but they did not report an overall lack of desire to be professional. 15 Ainsworth and Szauter 16 found that less than 10% of medical students with noted professionalism lapses did not acknowledge them and accept responsibility.…”
Section: Is the Resident Willing To Comply With Professional Expectatmentioning
confidence: 99%